HIV-1 induction of tolerogenic dendritic cells is mediated by cellular interaction with suppressive T cells - Svanberg, Cecilia; Nyström, Sofia; Govender, Melissa; Bhattacharya, Pradyot; Che, Karlhans F.; Ellegård, Rada; Shankar, Esaki M.; Larsson, Marie (Frontiers in Immunology, 2022)
HIV-1 infection gives rise to a multilayered immune impairment in most infected individuals. The chronic presence of HIV-1 during the dendritic cells (DCs) priming and activation of T cells promotes the expansion of suppressor cells in a contact dependent manner. The mechanism behind the T cell side of this HIV-induced impairment is well studied, whereas little is known about the reverse effects exerted on the DCs. Herein we assessed the phenotype and transcriptome profile of mature DCs that have been in contact with suppressive T cells. The HIV exposed DCs from cocultures obtained a more tolerogenic phenotype with increased expression of e.g., PDL1, Gal-9, HVEM, and B7H3, mediated by interaction with T cells. Transcriptomic analysis showed a type I IFN response profile as well as an activation of pathways involved in T cell exhaustion. Taken together, our data indicate that the prolonged and strong IFN type I signaling induced by the presence of HIV during DC-T cell cross talk could play an important role in the induction of the tolerogenic DCs and suppressed immune response.